THE HISTORICAL DEVELOPMENT AND EDUCATIONAL POTENTIAL OF PURA DESA BENGKALA AS A LOCAL HISTORY LEARNING RESOURCE IN SENIOR HIGH SCHOOLS - Ni Luh Weka Citra Damayanti; I Made Pageh; Ketut Sedana Arta (SOSIOEDUKASI, 2026)
Pura Desa Bengkala is one of the significant cultural heritage sites in Bali that embodies the historical continuity of Balinese Hindu civilization and local traditions. This study aims to examine the historical development of Pura Desa Bengkala, analyze its architectural structure and socio-religious functions, and evaluate its potential as a local history learning resource for senior high school students. The research employed a qualitative historical approach involving observation, interviews, and document analysis. Data were collected from local community leaders, temple administrators, historical records, and relevant literature. The findings reveal that Pura Desa Bengkala has evolved through a long historical process influenced by the interaction between indigenous Balinese beliefs and Hindu cultural traditions. Architecturally, the temple reflects the Tri Mandala spatial concept and contains various sacred structures that symbolize the cosmological values of Balinese Hinduism. Beyond its religious function, Pura Desa Bengkala serves as a center for social integration, cultural preservation, and the transmission of local wisdom within the community. The study further demonstrates that the temple possesses substantial educational value as a local history learning resource. Its historical background, cultural significance, architectural characteristics, and embedded values can enrich history learning by providing contextual and experiential educational opportunities. Integrating local historical heritage into classroom instruction can strengthen students’ historical awareness, cultural identity, and appreciation of regional heritage. Therefore, Pura Desa Bengkala represents an important educational resource that supports the implementation of local history-based learning in senior high schools and contributes to the preservation of cultural heritage through education.